The Role of Guidance and Counseling Teacher Services in Implementing Individual Counseling to Improve Learning Independence - Kholifah, Siti; Khoiriyah, Siti; Ismanto, Heri Saptadi; Yulianti , Padmi Dhyah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Education is an integral part of the development of national and state life, as stated in Law no. 20 of 2003 article l. However, there are several obstacles that occur in realizing education, including the lack of student learning independence. So the role of guidance and counseling teachers is needed in dealing with this problem. Therefore, researchers want to know the role of guidance and counseling teachers in carrying out individual counseling to increase student learning independence at SMAN 1 Mranggen. This research uses a qualitative research method design. The data collection technique in this research is by using direct observation, interviews and documentation. This data analysis uses the Milles and Huberman data analysis model, namely: data collection, data reduction, data presentation. Drawing conclusions/verification. In this research, the criteria for trustworthiness are used, namely: long-standing interest, persistent observation in research, and triangulation testing. The results obtained in the research show that: The role of the guidance and counseling teacher at SMAN 1 Mranggen is very useful for students who have problems. Guidance and Guidance Teachers have duties and responsibilities in guidance and counseling service activities for students. Guidance and counseling service activities at school are activities to help students find their identity. With the presence of a guidance and counseling teacher, students become better than before so that student learning independence can be handled well.